Role of bank lending in financing green projects: A dynamic stochastic general equilibrium approach - Maria Teresa Punzi (Asian Development Bank Institute (ADBI), 2018)
This paper develops an environmental dynamic stochastic general equilibrium (E-DSGE) model with heterogeneous production sectors. In particular, the model comprises some low-carbon emission firms that finance their investments and production only through banking loans, and high-carbon emission firms that finance their investments either with bank loans or by issuing equities. Moreover, government imposes intensity targets to reduce pollution, and high-carbon emission firms buy permits to allow their production. The model studies the transmission mechanism of technology, monetary, and financial shocks and finds that only a positive financial shock to green firms can boost production and credit for the green sector. A financial shock can be interpreted as the borrowing capacity of firms in terms of tightening or relaxing the enforcement of collateral constraints. In contrast, a positive technology shock and easier monetary policy lead only to a short output on impact, but in the longer term green firms experience losses. Later, the paper analyzes the impact of several macroprudential policies and finds that only differentiated capital requirements can help to sustain green financing.
Keywords: E32; E50; Q43; H23; 330; E-DSGE model; environmental policy; green financing; macroprudential policy